Designing Environmentally Sustainable Nursing Protocols: A Novel Framework to Reduce Carbon Footprint in Hospital Care Through Green Practice Integration - Witriyani Witriyani; Andriani Mei Astuti; Irba tartila Amtiyaz; Vijimol Vijimol (Green Health International Journal of Health Sciences Nursing and Nutrition, 2024)
This study explores the integration of green practices into nursing protocols as a means of reducing the environmental impact of hospital care. Hospitals significantly contribute to global carbon emissions, and nursing practices are integral to healthcare operations, yet they often lack sustainability considerations. The aim of this research was to develop and implement a set of green-practice guidelines tailored for nursing staff to minimize carbon emissions and improve operational efficiency. Through collaboration with environmental experts, nursing staff, and hospital management, new guidelines were established focusing on waste reduction, energy-efficient practices, and sustainable procurement. A waste-audit assessment was conducted to analyze current waste management practices, while a pilot implementation was carried out in selected hospital wards. The results revealed an 18% reduction in carbon emissions following the integration of these green practices into daily nursing activities. Key contributors to this reduction included waste segregation, the use of reusable medical supplies, and energy conservation measures such as optimizing lighting and HVAC systems. However, challenges such as resistance to change, resource limitations, and the need for specialized training were identified during the pilot phase. Despite these barriers, the research highlights the significant potential for nurses to lead sustainability efforts in healthcare settings. The findings indicate that integrating green practices into nursing protocols can provide environmental, operational, and economic benefits, ultimately contributing to more sustainable healthcare systems. Future research should refine these protocols, explore their broader application, and assess long-term outcomes across various healthcare settings